The Oral Traditions As Communication Media In Transforming Religious Culture Values At Bali-Hindu Community - I Wayan Ardhi Wirawan (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2022)
This study aims to conduct a study of the practice of oral traditions used as a medium of communication in the transformation of religious culture values at the Balinese-Hindu community in Lombok. This phenomenon is related to the decrease in the intensity of the practice of oral traditions in the midst of the modern communication media flow as a consequence of technological developments, especially information technology. This research is designed in an interpretive qualitative type in order to study the shift in the use of traditional cultural communication media, especially in practices of oral traditions. This study found that the influence of modern communication media which is increasingly widespread in the midst of people's lives with technology that is constantly evolving provides flexibility for people to access religious messages conveyed to the public. The development of modern information technology has a significant impact on the preservation of oral traditions created by past civilizations which have been handed down to the Balinese-Hindu society nowdays. In this regard, it is necessary to participate in cultural activists and related parties in order to build awareness about the importance of preserving oral traditions as a medium for communicating noble values ​​in religious culture.